SAE 1045 steel/WC-Co/Ni-Cu-Ni/SAE 1045 steel joints prepared by dynamic diffusion bonding: Microelectrochemical studies in 0.6 M NaCl solution - Andreatta, Francesco; Matesanz, Laura; Akita, Adriano H. [UNESP]; Paussa, Luca; Fedrizzi, Lorenzo; Fugivara, Cecilio Sadao [UNESP]; Gomez de Salazar, Jose M.; Benedetti, Assis Vicente [UNESP] (Pergamon-Elsevier B.V. Ltd, 2009)
Corrosion of SAE 1045 steel/WC-Co/Ni-Cu-Ni/SAE 1045 steel interfaces was investigated in 0.6 M NaCl solution using an electrochemical microcell, which enables local electrochemical characterization at the micrometer scale. Two pieces of steel, one with a WC-Co coating covered with Ni (12 mu m) and Cu (5 mu m) layers, and the other with a Ni (15 mu m) layer,were welded by dynamic diffusion bonding. AWC-Co coating was applied to the steel by the high velocity oxygen-fuel process, and Ni-Cu and Ni layers by electroplating. Polarization curves were recorded using an electrochemical microcell. Different regions of welded samples were investigated, including steel, cermet coating, and steel/cermet and steel/Ni-Cu-Ni/cermet interfaces. Optical and electronic microscopes were employed to study the corroded regions. Potentiodynamic polarization curves obtained using the microcell revealed that the base metal was more susceptible to corrosion than the cermet. In addition, cermet steel/cermet and steel/Ni-Cu-Ni/cermet joints exhibited different breakdown potentials. Steel was strongly corroded in the regions adjacent to the interfaces, while the cermet was less corroded. Iron oxides/hydroxides and chloride salts were the main corrosion products of steel. After removal of the superficial layer of corrosion products, iron oxides were mainly observed. Chloride ions were detected mainly on a copper-enriched layer placed between two Ni-enriched layers. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Microelectrochemistry; Cermet-carbon steel joints; Dynamic diffusion bonding; Potentiodynamic polarization; Welding